Cluster-based routing protocol in wireless sensor network - Ghanem, Shireen Bashar; Yonis, Aws Zuheer (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Wireless sensor networks (WSNs) play a crucial role in various domains, including military, industrial, and environmental applications, due to their capability to monitor and transmit data efficiently. However, one of the major challenges in WSNs is energy consumption, as sensor nodes rely on limited power sources for data acquisition, processing, and communication. Efficient energy management is essential to prolong network lifespan and maintain performance. To address this issue, several energy-efficient routing techniques have been developed. Among these, the low-energy adaptive clustering hierarchy (LEACH) has gained significant attention for its ability to optimize power consumption through hierarchical clustering. This study investigates the performance of the LEACH protocol under different deployment configurations. We proposed and evaluate a circular sensing field as an alternative to the traditional square and rectangular field. Simulation results show that the circular field achieves better energy efficiency and network longevity across various packet sizes and base station (BS) locations. These findings highlight the importance of deployment geometry in enhancing WSN sustainability.